2019
DOI: 10.1186/s12896-018-0496-0
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-218 promotes early chondrogenesis of mesenchymal stem cells and inhibits later chondrocyte maturation

Abstract: BackgroundMicroRNAs (miRNAs) reportedly participate in the mesenchymal stem cell (MSC) chondrogenic differentiation regulation. We objected to examine how miR-218 regulate chondrogenic differentiation of synovium-derived MSCs (SDSCs) and the maturation of RCJ3.1C5.1 chondrocytes. SDSCs were sourced from the knee joint synovium of New Zealand white rabbits, and their multilineage differentiation potentials were examined. The level of miR-218 was measured during SDSC chondrogenic differentiation, together with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 33 publications
0
30
1
Order By: Relevance
“…Accumulating evidence has shown that a number of miRNAs, including miR-140, miR-143, miR-145, miR-483, miR-181a, miR-218, and miR-410, play critical roles in hBMSC chondrogenic differentiation [15,23,25,40,44,45]. The miR-140, miR-143, miR-145, miR-181a, and miR-221 expression patterns during hBMSC chondrogenic differentiation in our conditions were in line with those reported in previous studies [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence has shown that a number of miRNAs, including miR-140, miR-143, miR-145, miR-483, miR-181a, miR-218, and miR-410, play critical roles in hBMSC chondrogenic differentiation [15,23,25,40,44,45]. The miR-140, miR-143, miR-145, miR-181a, and miR-221 expression patterns during hBMSC chondrogenic differentiation in our conditions were in line with those reported in previous studies [15].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of miR-145 in C3H10T1/2 cells reduced SOX9 expression, thus significantly suppressing cartilage matrix synthesis in vitro [20]. Additionally, miR-495, miR-92a, miR-483, miR-892b, and miR-218 have been found to play important roles in hBMSC chondrogenic differentiation [21][22][23][24][25]. Whether other miRNAs are involved in this process has not yet been clearly elucidated.…”
Section: Introductionmentioning
confidence: 99%
“… 20 Multiple studies have reported involvement of miRs in the pathogenesis of osteoarthritis such as miR-218, miR-365, miR-145 and miR-146a. 6 , 8 - 10 miR-152-3p is over-expressed in postmenopausal females reported with osteoporosis and fracture, fragile suggesting a link between miR-152 and osteoporosis affecting the osteoblasts differentiation. 12 miR-152 exerts inhibitory effect on the levels of cytokines like IL-12, IL-6 and the TNF-α, 13 in addition to this miR-152 blocks the expression of pro-inflammatory cytokines in Rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 99%
“… 5 - 7 miR-218 has been reported to promote the process of chondrogenesis of mesenchymal stem cells and also inhibited the later chondrocyte maturation by involving the HPGD pathway. 8 miR-365 has been found to target histone deacetylase- 4 and increases the process of chondrogenesis. 9 miR-145 have been reported to regulate the differentiation of chondrocytes in stem cells via the SOX9 pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Carriers have been employed to deliver miRNA-149-5p to MSCs to promote chondrogenesis (Celik et al, 2019). MiR-218 is highly expressed early in cartilage formation, but is stopped in synaptic-derived mesenchymal stem cells (SDSC) at the maturation stage of cartilage differentiation and miR-218 may directly regulates 15hydroxyprostaglandin dehydrogenase expression in SDSCs (Chen et al, 2019c). MiR-320c was decreased in the later stages of chondrogenesis of adipose-derived stem cells (hADSCs) and OA chondrocytes.…”
Section: Cartilagementioning
confidence: 99%